Towards a definition of crisis administration some sociological and legal notes on administering a community in extremis - Hipe, Victoriano A. (1975)
This essay will try to visualize public administration in the context of crisis. It will do so, as the title indicates, along sociological and legal lines, crisis being largely a sociological
phenomenon and crisis administration being theoretically circumscribed by legal restraints.
Keywords: Crisis management in government; Public administration